Revamping Strategies for Teaching English Language to Meet the Challenges of 21st Centuries Classroom in Nigeria - Obera, Joy; Ugboja, Anthony; Sule, Emah (American Journal of Literature Studies, 2023)
This paper examines revamping strategies for the teaching and learning of English language to meet the challenges of the 21st century's classroom. It demonstrates the need to improve the teaching strategies especially the innovative strategies that can aid the teaching and learning of English in the 21st century's classroom. Revamping these innovative strategies such as; creative task-based, blended learning, collaborative, flipped learning etc can help to resolve the challenges involved in the teaching and learning of English in the 21st century's classroom. The paper draws attention to the new trends in the 21st century's classroom that will bring about the desired change for effective teaching and learning of English language. The paper through the literature finds out that revamping the strategies will enable learners to be independent; it enhances the students' centered classroom which is a desired strategy in the 21st century's classroom. The paper concludes with the following suggestions: English teachers should blend the innovative teaching strategies with the conventional teaching methods so as to enhance learners' effective participation in the learning of English. Strategies that can increase learners' interest be adopted into the teaching of English language in other to overcome the challenges of teaching English in the 21st century's classroom. For effective revamping of the strategies for teaching and learning of English, there should be training and workshop for teachers in other to meet the challenges of teaching English in The 21st century' classroom.